Outbreak of Burkholderia Cepaciae Bacteremia in Neonatal Units of a Public Sector Hospital in Karachi, Pakistan - Shamaila Tasleem, Madiha Sattar Ansari, Azizullah Khan Dhillo, Sadia Ishaque, Sohaima Manzoor, Shehla Baqi, Habib Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: This study aimed to determine the occurrence of Burkholderia cepaciae outbreak in neonatal units, identifying the source, defining the best therapy for B. Cepaciae, and enhancing infection control practices. Methods: All neonates with BCC bacteremia during the study period were included. Data were gathered through the microbiology database, medical charts, laboratory data, and infection control surveys. Disk diffusion methodology was used in accordance with CLSI. Information from environmental cultures and feedback was included in the study. Results: The results showed varying patient demographics across the three pediatric wards, with differences in weight, gender distribution, hospital stay duration, and diagnoses. Trends of outbreak were identified with varying patterns in different wards. An intervention was performed, leading to general improvements in infectious disease control practices, and Burkholderia cepaciae was found to be most sensitive to Levofloxacin and Trimethoprim-Sulfamethoxazole. Conclusion: The study identified suspected sources and defined susceptibility profiles for empirical therapy for B. Cepaciae, contributing to the prevention of future outbreaks. Challenges in implementation underscore the need for proper administration and continuous emphasis on correct implementation of infection control practices. Keywords: BCC bacteremia, neonates, outbreak, Burkholderia cepaciae, infection control practices, Civil Hospital Karachi.